Evidence of an additional centre of apple domestication in Iran, with contributions from the Caucasian crab apple Malus orientalis Uglitzk. to the cultivated apple gene pool. Issue 21 (15th September 2022) - Bina, Hamid; Yousefzadeh, Hamed; Venon, Anthony; Remoué, Carine; Rousselet, Agnès; Falque, Matthieu; Faramarzi, Shadab; Chen, Xilong; Samanchina, Jarkyn; Gill, David; Kabaeva, Akylai; Giraud, Tatiana; et al.
Abstract: Divergence processes in crop‐wild fruit tree complexes in pivotal regions for plant domestication such as the Caucasus and Iran remain little studied. We investigated anthropogenic and natural divergence processes in apples in these regions using 26 microsatellite markers amplified in 550 wild and cultivated samples. We found two genetically distinct cultivated populations in Iran that are differentiated from Malus domestica, the standard cultivated apple worldwide. Coalescent‐based inferences showed that these two cultivated populations originated from specific domestication events of Malus orientalis in Iran. We found evidence of substantial wild‐crop and crop–crop gene flow in the Caucasus and Iran, as has been described in apple in Europe. In addition, we identified seven genetically differentiated populations of wild apple ( M. orientalis ), not introgressed by the cultivated apple. Niche modelling combined with genetic diversity estimates indicated that these wild populations likely resulted from range changes during past glaciations. This study identifies Iran as a key region in the domestication of apple and M. orientalis as an additional contributor to the cultivated apple gene pool. Domestication of the apple tree therefore involved multiple origins of domestication in different geographic locations and substantial crop‐wild hybridization, as found in other fruit trees. This study also highlights the impact of climate change on the natural divergence of a wild fruit tree and provides a starting point for apple conservation and breeding programmes in the Caucasus and Iran.